Design And Development of Car Sparepart Sales Information System For Web-Based Using RAD Method On UMKM Sinar Seroja - Steven Chandra; Rudi Sutomo; Jansen Wiratama (G-Tech: Jurnal Teknologi Terapan, 2023)
UMKM A business that deals in auto accessories and parts is called Sinar Seroja. UMKM Sinar Seroja wishes to create an integrated system because errors frequently occur in the data collection and processing of traditional sales transaction data, namely inventory data with sales transaction data in a traditional system that is not integrated. This makes it tough to record and process data regarding inventory and sales transactions. Rapid Application Development (RAD) is a technique used to create a web-based integrated sales information system. This was proven after the Black Box testing was carried out with an average result of 88.3% indicating that the web-based application had been successfully implemented.Customers may get around current issues so that it is simpler to save and handle sales and warehousing transaction data with an integrated web-based sales information system. Additionally, Sinar Seroja needs a system to be developed as a medium for transaction data storage because it.